PENGARUH METODE MAKE A MATCH DENGAN MEDIA GAMBAR TERHADAP KEMAMPUAN MENGENAL KEKHASAN BANGSA INDONESIA SEPERTI KEBHINEKAAN SISWA KELAS III SDN PURWODADI KEC. KRAS KAB. KEDIRI TAHUN AJARAN 2015 - LINGGA DEWI, RISKE NURALITA; LAILA, ALFI (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2015)
The background of this research observations and experiences research. that teaching Civics in particular in Purwodadi SDN 1 has not been implemented to the maximum. It can be seen from the average grade Civics subjects were lower compared with the other subjects. This is because learning in the classroom is still dominated by the teachers. and less variation of the method and model of applied learning in the classroom teacher. As a result. students tend to be passive in accepting the lessons. The problems of this study are (1) Is the lecture with media images affect the ability to know the diversity of students? (2) Does the method make a match with media images affect the students' ability to recognize the diversity of the class? (3) Are there differences in the effect of a lecture with media images rather than methods of make a match with the media image of the ability of the student Diversity Know? This research uses experimental research technique so that there are two classes. experimental and control. Using a quantitative approach to research subjects third grade students of SDN Purwodadi 1. Data collection techniques in the form of a test. and the instrument be a matter of stuffing. The data analysis technique used is inferential statistics using independent t-test at 5% significance level. Results of the analysis carried out showed the value of t (3.486) and the average value of the control class (73.92) <75 (KKM). while the average value of the experimental class (85.04)> 75 (KKM). That is no effect of the learning model make a match with the media image of the ability to recognize the diversity of third-grade students of SDN Purwodadi I Kediri